The Study of Oral Liquid Microcrystallization in Children with Gastro-Esophageal Reflux Disease - SPINEI, AURELIA (Clujul Med, 2014)
BACKGROUND AND AIM. Patients with disabilities have a higher prevalence of caries and dental erosions than general population. This particularity may be assessed by the study of microcrystallization of saliva. We investigated the oral liquid microcrystallization in children with gastroesophageal reflux disease (GERD), a condition associated with dental erosions. MATERIAL AND METHODS. 54 children have been clinically examined: 27 children suffering from GERD with ages between 13 and 15, were included in the study group, and 27 healthy children - the control group. The study of crystallographic changes of the oral liquid was performed using the method developed by Shatohina, Razumov SN, Shabalin VN (2006) with the scanning electron microscope VEGA TESCAN TS 5130 MM. RESULTS: The degree of microcrystalization of the oral liquid in children with GERD was considerably reduced, (1.73±0.11 points) and was lower than in children in the control group (3.22±0.16 points) (p<0.01, RR=2). The degree of microcrystallization of oral liquid in children with GERD was 1.86 times lower than in healthy children. This was correlated with the duration of gastroesophageal reflux. CONCLUSION: The study of structural particularities of dehydrated droplet of oral liquid in children with GERD has elucidated a number of markers of the changes produced in the oral cavity. These can be used in the screening research in prevention of caries and dental erosions.